Liturgical Training and Youth Fellowship Development in Realising Meaningful Worship - Banga, Berthin S; Maahury, Yane R.; Roragabar, Yeni I.; Tolanda, Yofsan; Ferre, Godfried San; Bandong, Yohanes; Lantaka, Okrisye; Hutasoit, Resmi; Gobai, Mika; Hutapea, Melina; Irianto, Irianto; Lesirolo, Tresia F; Limbong, Ayulita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community engagement program responds to the declining participation of young congregants in meaningful worship at GKI Hermon Hollo Him. The activity aimed to strengthen the role of young liturgists and nurture the spiritual formation of the youth fellowship. Using a structured approach, including needs assessment, contextual material design, lectures, demonstrations, guided practice, and reflective discussions, the program equipped participants with theological insight and practical liturgical skills. Evaluation was conducted through questionnaires to measure comprehension and responses toward the training. The results show a marked improvement: most participants gained a deeper understanding of liturgy as a transformative encounter with God and demonstrated increased confidence in leading worship. The program successfully integrated theological learning and liturgical practice, enabling young members to serve with greater awareness, competence, and spiritual maturity. In conclusion, the activity effectively empowered youth as active agents in realizing meaningful and life-giving worship within the congregation.